Optimizing Single Axis Tracking for Bat Algorithm-based Solar Cell - Ali, Machrus; Fahmi, Tubagus; Wida Khaidir, Delief; Nurohmah, Hidayatul; Budiman, Budiman (Universitas Negeri Malang, 2020)
Adding the solar tracking control system was an attempt to increase the efficiency of solar panels. The solar tracking control system was a control system that follows the sun position. The purpose of this solar tracking system was to position the cross-section always to face the sun. The Single Axis system in solar tracking was intended to follow the sun’s angle or solar azimuth angle from the east to the west. There needed a control optimization to get the position as desired. Optimization often used artificial intelligence to obtain the automatic best optimization, such as Bat Algorithm (BA). This research compared several methods: without control, using PID control, using PID-Auto control, and using PID-BA control. The simulations showed that the smallest elevation angle deviation was found in PID-BA controller. In conclusion, PID-BA was the best controller in this research. This research could be used as a future reference with other controllers to get the most optimized controller.